Characteristics, distribution and morphogenesis of subtidal microbial systems in Shark Bay, Australia - Jahnert, R.; Collins, Lindsay (Elsevier Science BV, 2012)
The distribution, nature and extent of microbial deposits in Hamelin Pool, Shark Bay have been investigated and mapped with emphasis on the occurrence, external morphologies, internal fabrics, constructional mechanisms, microbial communities, growth rates and sediment associations in the intertidal and previously little researched subtidal zone. Detailed georeferenced substrate mapping revealed extensive subtidal microbial deposits occupying approximately 300 km2 of the total Holocene 1400 km2 area of Hamelin Pool. The Microbial Pavement covers 227 km2 of the subtidal substrate that together with columnar structures reveals a subtidal microbial habitat which occupies an area 10 times larger than the area of the intertidal deposits. Microbial carbonate is composed of aragonite (80–98%) that reveals high positive values of δ13C (+4.46 to +5.88) and δ18O (+3.06 to +3.88) as a characteristic of the highly evaporative environment with extensive microbial activity. Oldest dated heads are 1915 and 1680 14C years BP, and the overall system was deposited in two stages; the first between 2000 and 1200 and the last from 900 years BP to the present. Slow growth rates vary from less than 0.1 mm/year to 0.5 mm/year. Different internal fabrics were constructed according to their position in relation to the littoral zone by distinct microbial communities, and lateral fabric relations have been established.Evidence of shallowing upward fabric sequences of microbial origin reflects relative falling sea levels during the late Holocene and is likely useful in ancient environmental interpretation. A sequence of events and mechanisms are described emphasizing differences between the stromatolitic, thrombolitic and cryptomicrobial deposits in Shark Bay. The new substrate map and depositional history for this distinctive and peculiar microbial habitat establish the significance of subtidal structures and emphasize the geoscientific importance of Hamelin Pool, especially with respect to early life studies and ancient analogues for understanding microbial activity, deposit characteristics, fenestral fabrics and distribution.